2010
DOI: 10.2118/133206-pa
|View full text |Cite
|
Sign up to set email alerts
|

Is High-Pressure Air Injection (HPAI) Simply a Flue-Gas Flood?

Abstract: High-pressure air injection (HPAI) is an enhanced oil recovery (EOR) process in which compressed air is injected into a deep, light-oil reservoir, with the expectation that the oxygen in the injected air will react with a fraction of the reservoir oil at an elevated temperature to produce carbon dioxide. Over the years, HPAI has been considered a simple flue-gas flood, giving little credit to the thermal drive as a production mechanism. The truth is that, although early production during a HPAI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 23 publications
3
11
0
1
Order By: Relevance
“…At 200°C, bond scission begins to predominate in LTO reaction to form the carbon dioxide and water, which leads to the decreasing diversity of oil mass loss in air and nitrogen flow. As a result, the total mass loss of oil in presence of air is greater than that of nitrogen during the period of temperature reaching to 360°C Montes et al(2010). pointed out that oxygen addition reaction usually occurred at about 150°C below while the bond scission occurred in 250-300°C,which was close to the experimental results of this paper.…”
supporting
confidence: 89%
“…At 200°C, bond scission begins to predominate in LTO reaction to form the carbon dioxide and water, which leads to the decreasing diversity of oil mass loss in air and nitrogen flow. As a result, the total mass loss of oil in presence of air is greater than that of nitrogen during the period of temperature reaching to 360°C Montes et al(2010). pointed out that oxygen addition reaction usually occurred at about 150°C below while the bond scission occurred in 250-300°C,which was close to the experimental results of this paper.…”
supporting
confidence: 89%
“…Laboratory combustion tube tests indicate that the thermal front is an important displacement mechanism for light oils. As described by Montes (2010), fluid recovery (oil plus water) is almost in direct proportion to the volume burned. This behavior was implied by Erickson (1994) in his landmark paper introducing the air injection process in the Williston Basin.…”
Section: Field Design Considerationsmentioning
confidence: 94%
“…Simultaneously, the content of the CO 2 in the effluent gas reached up to approximately 15 %. According to Montes et al, 33 a CO 2 level of exceeding 12% indicated that combustion-like reactions occurred. The above-mentioned data implied that the combustion reaction was dominated for the further oxidation of the formed coke.…”
Section: Fuel Deposition In the Oxidation Process In Isothermal Oxidamentioning
confidence: 99%